The Optimization Analysis of Sports Industry Experience Consumption Ability under the Theory of Aesthetic Economy - Rongrong Wang (Discrete Dynamics in Nature and Society)
The consumption ability of the sports industry is an indicative index of sports economic development, and aesthetic economic theory plays a guiding role in this content. At present, the evaluation method of sports industry consumption ability is too single, lack of the comprehensive evaluation model, and cannot carry out accurate evaluation. This study proposes a comprehensive improved algorithm based on K-mean preprocessing, which can evaluate and judge the consumption capacity of the sports industry with the help of aesthetic economic theory, and provides support for the later formulation of experience consumption strategy. MATLAB simulation results show that the accuracy of the calculation results of the improved algorithm proposed in this study is more than 95%, and the fit between consumption ability evaluation indexes is more than 98%, which is better than the traditional algorithm as a whole. Therefore, the comprehensive improved algorithm can optimize the consumption capacity of the sports industry.